Planning an Information System for Health Services - HÄRÖ, A. S. (Methods of Information in Medicine, 1972)
The close relationship between planning and information services is discussed and some recent activities are referred to. Four types of information systems — the expert system, the traditional statistical system, the integrated problem-oriented system of databanks and the all-comprehensive databank — are described and their advantages and disadvantages summarised. The interrelationships between type of society and planning on the one hand and between planning and information systems on the other hand are discussed and a combined type of information system (experts plus traditional statistics plus databanks) is recommended. The use of norms and indicators is discussed and the structure and weak points of the various approaches in planning are described, To some extent, normative (deductive) planning is practicable in any type of society, but in many areas inductive planning is better suited to modern industrialised societies. In any case, information is a prerequisite to systematic planning. Health affairs are considered to be one of the elements of general national information systems, but the greater part of health-related information can be used for administrative and practical decisions on a lower level only. Suitable decentralisation prevents too great an escalation of combinations and makes it possible to fulfil the main requirement: to give adequate and objective service to all those who have to make decisions.The construction of an information service based on »system analysis« is recommended which pays special attention to decisions, and an example from the hospital field is given. The producer-orientation of the information system presented is noted and the necessity for more consumer-oriented complementary systems for basic problems related to matters of health and our mode of living is stressed.Die engen Beziehungen zwischen Planung und Informationsdiensten werden behandelt und einige neuere Aktivitäten aufgezeigt. Vier Typen von Informationssystemen — das Expertensystem, das traditionelle statistische System, das integrierte problem-orientierte System der Datenbanken sowie die allumfassende Datenbank — werden beschrieben und ihre Vor- und Nachteile gegenübergestellt. Die Interrelationen zwischen Gesellschaftsform und Planungsform einerseits und zwischen Planung und Informationssystemen andererseits werden behandelt und eine kombinierte Form eines Informationssystems (Experten plus traditionelle Statistik plus Datenbanken) wird empfohlen. Die Anwendung von Normen und Indikatoren wird behandelt und die Struktur und die Schwachstellen von verschiedenen Planungsmethoden werden beschrieben. In gewissem Umfang ist die normative (deduktive) Planung bei allen Gesellschaftsformen anwendbar; aber auf einigen Gebieten ist eine induktive Planung für die moderne Industriegesellschaft besser geeignet. Jedenfalls ist Information eine Voraussetzung für systematische Pia-nung. Das Gesundheitswesen ist als ein Grundbestand allgemeiner nationaler Informationssysteme anzusehen; aber ein Großteil der einschlägigen Informationen läßt sich nur für administrative und praktische Entscheidungen auf relativ niedriger Ebene anwenden. Eine adäquate Dezentralisierung verhindert eine zu große Eskalation von Kombinationen und ermöglicht die Erfüllung der Hauptforderung, nämlich all denen adäquat und objektiv dienlich zu sein, welche Entscheidungen zu treffen haben.Der Aufbau eines auf »Systemanalyse« basierenden und speziell auf Entscheidungen ausgerichteten Informationsdienstes wird empfohlen; ein Beispiel aus dem Krankenhauswesen wird angeführt. Es wird ausdrücklich betont, daß dieses Informationssystem hersteller-orientiert ist, und es wird die Notwendigkeit hervorgehoben, mehr verbraucher-orientierte Systeme für Grundprobleme im Zusammenhang mit dem Gesundheitswesen und unserer Lebensform zu schaffen.
Keywords: Health Services; Health Information Systems; Planning Information Systems; Integrated Problemoriented Databanks